Risk Factors of Narcotic and Psychoactive Drugs Use among University and High School Student - Ali Kashi; Zahra Sarlak (Drug Control Headquarters, Research and Education Office, 2010)
Aim: Today use of different banned substances such as narcotic, psychoactive and energetic drugs are social problem that has created worry in different levels of human societies. The aim of present study was examined the prevalence of use of narcotic and psychoactive drugs among high school and university students also identifying of risk factors associated with the use of this materials. Method: The population of this descriptive survey study was all students of high school and university of Khodabandeh city. By cluster random sampling 580 students of high school and university selected and questionnaires distributed among them. After eliminating incomplete questionnaires 480 students remained as research sample. Results: In consideration of selected sample the most important reasons of using of narcotics are: enjoying and curiosity, exposed to bad environment like addicted friends and families, joblessness, economic problems, lack of information and loss of affection. Conclusion: The analysis of the results indicated the high prevalence of narcotic and drugs use and necessity of codification of preventive programs for these people.